The Existence of the Music Concert Phenomenon: Deviant Behavior of Adolescents - Fatimah, Nurma; Mudzakkir, Moh. (Paradigma, 2025)
The existence of music concerts is never timeless, even though it was vacuumed for 2 years due to the COVID-19 pandemic that hit. However, with the existence of music concerts that continue to show an increase, it actually has an impact on the public's perspective regarding teenagers who watch the concert because deviant behavior has also increased so that people give labeling or giving a negative connotation. Based on the research, the results show that there is a relationship between the existence of music concerts and deviant behavior by adolescents based on existing factors. And there is labeling given by the community to young people who like music concerts. This can lead to negative connotations in the social environment experienced by the individual. So it can be justified the existence of community labeling of teenagers because it is influenced by the existence of music concerts with deviant behavior in it.